Automated Decellularization of the Rodent Epigastric Free Flap: A Comparison of Sodium Dodecyl Sulfate–Based Protocols - Bengur, Fuat Baris; Chen, Lei; Schilling, Benjamin K.; Komatsu, Chiaki; Figlioli, Grace M.; Marra, Kacey G.; Kokai, Lauren E.; Solari, Mario G. (Journal of Reconstructive Microsurgery, 2022)
Background Free tissue transfer to cover complex wounds with exposed critical structures results in donor-site morbidity. Perfusion decellularization and recellularization of vascularized composite tissues is an active area of research to fabricate complex constructs without a donor site. Sodium dodecyl sulfate (SDS)-based protocols remain the predominant choice for decellularization despite the deleterious effects on tissue ultrastructure and capillary networks. We aimed to develop an automated decellularization process and compare different SDS perfusion times to optimize the protocol.Methods A three-dimensional-printed closed-system bioreactor capable of continuously perfusing fluid through the vasculature was used for decellularization. The artery and vein of rat epigastric fasciocutaneous free flaps were cannulated and connected to the bioreactor. Protocols had varying durations of 1% SDS solution (3, 5, and 10 days) followed by 1 day of 1% Triton X-100 and 1 day of 1x phosphate-buffered saline. The residual DNA was quantified. Microarchitecture of the constructs was assessed with histology, and the vascular network was visualized for qualitative assessment.Results The structural integrity and the microarchitecture of the extracellular matrix was preserved in the 3- and 5-day SDS perfusion groups; however, the subcutaneous tissue of the 10-day protocol lost its structure. Collagen and elastin structures of the pedicle vessels were not compromised by the decellularization process. Five-day SDS exposure group had the least residual DNA content (p < 0.001). Across all protocols, skin consistently had twice as much residual DNA over the subcutaneous tissues.Conclusion A compact and integrated bioreactor can automate decellularization of free flaps to bioengineer regenerative constructs for future use in reconstruction of complex defects. A decellularization protocol with 5 days of 1% SDS exposure was the most successful to keep the residual DNA content at a minimum while preserving the structural integrity of the tissues.
Keywords: decellularization; vascularized tissue engineering; fasciocutaneous free flap; extracellular matrix; allograft